Profile on status epilepticus, clinical features and lab parameters and outcome in pediatric intensive care - T., Arun prakash; K., Shruthi T.; S., Rajakumar P.; S., Shuba (International Journal of Contemporary Pediatrics, 2017)
Background: Status Epilepticus is a major medical and neurological emergency. Despite advance in treatment, it is still associated with mortality and morbidity. The objective of the study was to estimate the profile of status epilepticus on clinical features, lab parameters and outcome of the children admitted in pediatric intensive care. Methods: Children between 1 month to 18 years who were fulfilling the definition of status epilepticus and who were admitted in PICU in Sri Ramachandra Medical Center were included in the study. All the children who met inclusion criteria were taken for the study. history and physical examination was done for all the children with blood samples, CSF samples, urine sample, computerized tomography scan, EEG details were collected after getting informed consent. Results: Among 50 children 60% were in the age group were less than 5 years ,22% were between 6-10 years ,14% were between 11-15 years and 4% were above 16 yrs. The mean age group was 5.74 years (SD±4.75). Incidence was higher in males (54%) when compared to females (46%). Forty-seven children (94%) were brought to casualty with status epilepticus whereas three children developed SE in hospital. CSF study was done among 19 (38%) of the children in which CSF was found normal among 16(84%). CT scan/MRI brain findings were abnormal in (34%) and normal in 10 (66%) patients. Epilepsy was the most common diagnosis noted in 29 (58%) patients and febrile seizure was second common etiology noted in 12 (24%) in this series. In this series 47 (94%) patients were treated and discharged home, 2 (4%) patients died and one patient went against medical advice without follow up. Conclusions: Status epilepticus is one of the common neurological emergency which requires admission to PICU. In our study epilepsy is one of the most common causes of status epilepticus. Early and appropriate treatment with anticonvulsants and use of mechanical ventilation may improve the outcome.